2018
DOI: 10.1021/jacs.7b10453
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Reveals Deposition of Metal Oxide Coatings onto Metal–Organic Frameworks

Abstract: Postsynthetic strategies for modifying metal-organic frameworks (MOFs) have proven to be an incredibly powerful approach for expanding the scope and functionality of these materials. Previously, we reported on the postsynthetic exchange (PSE) of metal ions and ligands in the University of Oslo (UiO) series of MOFs. Detailed characterization by several analytical methods, most notably inductively coupled plasma mass spectrometry and transmission electron microscopy reveal that metal ion deposition on the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 43 publications
(69 reference statements)
1
49
0
2
Order By: Relevance
“…16,[32][33][34][35] One recent example with transition metals in MOF-5 involved the installation of Fe(OH) 3 (H 2 O) 2 moieties bridging SBUs on two interpenetrated lattices, 36 with limited additional examples focusing on alkali metal decoration of MOF-5. [37][38][39][40][41][42] These ndings point to a previously unrecognized divergence in the reactivity of early and late transition metals with oxygen-based SBUs: whereas the late transition metals favor cation exchange reactivity (the Zr-based MOFs notwithstanding 43 ), we show here that the high-valent early transition metals prefer to adhere to the SBU rather than exchange within the SBU, presumably because of their extreme oxophilicity. Notably, MOF-5 is a rare instance that allows both processes to occur.…”
Section: Resultssupporting
confidence: 48%
“…16,[32][33][34][35] One recent example with transition metals in MOF-5 involved the installation of Fe(OH) 3 (H 2 O) 2 moieties bridging SBUs on two interpenetrated lattices, 36 with limited additional examples focusing on alkali metal decoration of MOF-5. [37][38][39][40][41][42] These ndings point to a previously unrecognized divergence in the reactivity of early and late transition metals with oxygen-based SBUs: whereas the late transition metals favor cation exchange reactivity (the Zr-based MOFs notwithstanding 43 ), we show here that the high-valent early transition metals prefer to adhere to the SBU rather than exchange within the SBU, presumably because of their extreme oxophilicity. Notably, MOF-5 is a rare instance that allows both processes to occur.…”
Section: Resultssupporting
confidence: 48%
“…Soaking UiO-66 in an N , N ′-dimethylformamide (DMF) solution containing a Ti 4+ or Hf 4+ salt was initially reported to lead to the formation of mixed-metal SBUs by partial exchange of zirconium in the Zr 6 O 4 (OH) 4 (-COO) 12 SBUs ( 57 ). It was, however, later shown that metal ion exchange does not occur, but a metal oxide coating of titanium and hafnium, respectively, is formed ( 58 ). This may be ascribed to the strong M 4+ –O bonds in Zr 6 O 4 (OH) 4 (-COO) 12 SBUs, and metal ion exchange reactions are more likely to occur in SBUs with weaker M–O bonds.…”
Section: Framework Chemistry At the Sbusmentioning
confidence: 99%
“…The formation of titanium MOFs through partial cation exchange of parent zirconium MOFs has been reported. However, despite the incorporation of titanium into the materials is accomplished, there is controversy regarding the actual location of the titanium cations, and recent studies indicate that the addition of titanium cations takes place through a grafting process into the SBU or in the form of nanoscale surface deposited titanium oxide, rather than an actual cation exchange in the SBU. This is in line with computational studies that correlates the energetic stability of bimetallic MOFs, showing that the titanium/zirconium metal exchange is not energetically favourable …”
Section: Post‐synthetic Metal Exchangementioning
confidence: 99%